2022
DOI: 10.1002/ddr.22010
|View full text |Cite
|
Sign up to set email alerts
|

Ulinastatin ameliorates the malignant progression of prostate cancer cells by blocking the RhoA/ROCK/NLRP3 pathway

Abstract: Prostate cancer is a male malignant tumor disease with high incidence and mortality. This study was designed to explore the effects of ulinastatin (UTI) on the malignant progression of prostate cancer and its relevant mechanism of action. Human prostate cancer cell line PC‐3 was applied to investigate the anticancer activity of UTI. PC‐3 cells were treated with increasing concentrations (400, 800, and 1600 U/ml) of UTI. Cell proliferation, migration, invasion, and apoptosis were determined by cell counting kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…A recent experiment showed that UTI tended to suppress proliferation, migration, and invasion of cells but promoted apoptosis in PC-3 cells at higher concentrations. Moreover, UTI blocked RhoA and ROCK-mediated NLRP3 inflammasome activation in PC-3 cells [126].…”
Section: Compounds and Targets That Induce Apoptosis And Pyroptosis I...mentioning
confidence: 88%
“…A recent experiment showed that UTI tended to suppress proliferation, migration, and invasion of cells but promoted apoptosis in PC-3 cells at higher concentrations. Moreover, UTI blocked RhoA and ROCK-mediated NLRP3 inflammasome activation in PC-3 cells [126].…”
Section: Compounds and Targets That Induce Apoptosis And Pyroptosis I...mentioning
confidence: 88%
“…The proliferation and metastasis of tumor cells were closely related to the overexpression of the Rho protein. RhoA protein is highly expressed in gastric cancer [ 52 , 53 ], breast cancer [ 54 ], colon cancer [ 55 ], pancreatic cancer [ 56 ], lung cancer [ 57 ], and other cancers. The previous study of liver cancer showed that overexpression of the RhoA protein could facilitate the migration and invasion of liver cancer cells [ 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%